2020
DOI: 10.13106/jafeb.2020.vol7.n10.741
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Working Capital Management on the Profitability of Steel Companies on Vietnam Stock Exchanges

Abstract: This study examines the influence of working capital management (WCM) factors on the profitability of steel companies listed on the Stock Exchange of Vietnam. Data was collected from audited financial statements of companies for a period of 10 years, from 2010 to 2019. The number of samples eligible for research is 20 out of 26 companies, which is equivalent to 76.9%. With the help of dedicated software Stata version 14, the impact determination of WCM (through 8 independent variables: DIO, DPO, DSO, CCC, SIZ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 40 publications
5
22
0
Order By: Relevance
“…Debt utilization (LEV) has a negative relationship with ROA and is statistically significant. These results are consistent with those of studies done previously in other countries, such as the study of Deloof (2003); Ionnis and Lazaridis (2006); Garcia-Turuel and MartinezSolano (2007); Dong (2010), Enqvist et al (2014), Mielcarz et al (2018), Pham et al (2020), Oseifuah (2018) and Ngwenya (2012), Pattiruhu and Paais (2020) show that ROA has a positive and significant impact on dividend policy. 4 above is the results of model 2 regression, with dependent variable is GOP.…”
Section: Research Resultssupporting
confidence: 92%
“…Debt utilization (LEV) has a negative relationship with ROA and is statistically significant. These results are consistent with those of studies done previously in other countries, such as the study of Deloof (2003); Ionnis and Lazaridis (2006); Garcia-Turuel and MartinezSolano (2007); Dong (2010), Enqvist et al (2014), Mielcarz et al (2018), Pham et al (2020), Oseifuah (2018) and Ngwenya (2012), Pattiruhu and Paais (2020) show that ROA has a positive and significant impact on dividend policy. 4 above is the results of model 2 regression, with dependent variable is GOP.…”
Section: Research Resultssupporting
confidence: 92%
“…Musau (2015), Fernández-López et al (2020, Serrasqueiro (2014), and Jayarathne (2014) investigated a negative relationship between the DIO and firm's profitability. On the contrary, Pham et al (2020), Kusuma andBachtiar (2018), andTahir et al (2016) found a positive relationship between the variables. On the basis of previous studies, we propose the following hypothesis about the DIO: H 2A : There is a significant relationship between DIO and firm profitability.…”
Section: Days Inventory Outstanding (Dio) and Firm's Profitabilitymentioning
confidence: 76%
“…In this way, the firms rise their WC and free cash flow. Kayani et al (2020), Pham et al (2020), Musau (2015), and Mathuva (2012) found a positive impact of DPO on firms' profitability. On the other hand, Moussa (2018), Javid and Dalian (2014), and Serrasqueiro (2014) found a negative impact of DPO on firm profitability.…”
Section: Days Payable Outstanding (Dpo) and Firm's Profitabilitymentioning
confidence: 93%
See 2 more Smart Citations